Genetic understanding of vascular anomalies: better classification and risk‐stratification with targeted therapeutic options – a new horizon for vascular anomaly patients. (10th May 2022) - van der Vleuten, C.J.M.
Abstract : Linked article: F.N. El Sissy et al. J Eur Acad Dermatol Venereol 2022; 36 : 905–912. https://doi.org/10.1111/jdv.18046 .